Energy, exergy, sustainability and economic analysis of waste tire pyrolysis oil blends with different nanoparticle additives in spark ignition engine. (15th July 2022) - Yaqoob, Haseeb; Teoh, Yew Heng; Sher, Farooq; Jamil, Muhammad Ahmad; Ali, Mubbashar; Ağbulut, Ümit; Salam, Hamza Ahmad; Arslan, Muhammad; Soudagar, Manzoore Elahi M.; Mujtaba, M.A.; Elfasakhany, Ashraf; Afzal, Asif
Abstract: Fossil fuels are the primary source of energy for most industries worldwide. However, its resources are finite and declining day by day, and toxic gases are released due to their consumption which causes global warming and problems with the health of the living. Therefore, any alternatives to fossil fuels or any additives added to the fuel needed to be found to minimize fuel consumption and the emission of harmful gases. In this study, a spark-ignition engine fuelled with blends of petrol with different concentrations of graphite nanoparticles, Fe2 O3 nanoparticles, and tire pyrolysis oil (TPO) were used to conduct energy, exergy, economic, and sustainability analyses, and the obtained results were compared with neat petrol. The blends of petrol with 40 mg/L, 80 mg/L, and 120 mg/L of graphite nanoparticles & Fe2 O3 nanoparticles, as well as 5% & 10% TPO, were used in a single-cylinder, four-stroke, air-cooled SI engine in this study. The experiments were conducted on various engine loads of 2 Nm to 10 Nm with an increment of 2 Nm at a constant speed of 3500 rpm. The maximum exergy and energy efficiencies were obtained 23.05% and 21.94% at a load of 8 Nm when the testengine fired with the P120FO blend, respectively. A maximum sustainability index of 1.3 for the P120FO blend was obtained. A minimum exhaust energy rate of 0.03241 kW was obtained for P120FO. A minimum exhaust exergy rate of 0.005849 kW was obtained for P90T10. Best results in energy efficiency, exergy efficiency, sustainability index, and economic analysis were obtained for the P120FO blend compared to neat petrol. Finally, it was concluded that the addition of nanoparticles in fossil fuel increases the engine's efficiency, decreases fuel consumption, and reduces the emission of harmful gases. Highlights: Engine's response on the petrol blended with iron oxide/graphite nanoparticles and tire pyrolysis oil was analyzed. Investigating the blended fuels' energy, exergy, sustainability, and economic parameters. Petrol+120 mg/L Fe2 O3 (P120FO) is better than the other fuels in terms of energy and exergy.